ANALISIS SPASIAL LEPTOSPIROSIS DAN FAKTOR RISIKONYA DI KABUPATEN KLATEN - , Desy Ari Apsari; , Prof. drh. Setyawan Budiharta, MPH, PhD, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Leptospirosis is a zoonotic, that occurs in many part of the world, most countries in Southeast Asia declared as endemic areas of leptospirosis. Indonesia is a country with high case fatality rate of leptospirosis reaching 7.1%, with a range between 2.5 - 16, 45%, in patients aged over 50 years the mortality rate can reach 56%. Klaten district includes one of the distribution of leptospirosis. Data in 2008 showed that 21 were positively infected by leptospires of 66 people under investigation. In 2010 there were 5 deaths from 15 cases were found. Cases continue to rise in 2011 and expanded in several villages and districts, especially areas that are near the area of rice fields and streams. Objective: Knowing the distribution pattern of leptospirosis and risk factors in Klaten. Research methods: An observational study, design with a combination of ecological and case-control study. Implemented in Klaten in 2011. Subjects were residents who are diagnosed of leptospirosis or infected by Leptospira. Diagnosis is confirmed by a doctor based on clinical criteria of WHO-1982 and diagnostic test equipment (leptotek or MAT). Samples were taken of 210 people consisting of 105 cases and 105 controls. Analysis of data used is average nearest neighbor, Mc. Nemar and Conditional logistic regression(CI: 95%). Results: The pattern of distribution of leptospirosis in Klaten clustered at coordinates 454 230, 9.15211 UTM zone 49S, a radius of 423.86 meters. Risk factors for leptospirosis in Klaten is house sanitation (OR = 7.89, 95% CI: 2.68 to 23.21, p = 0.000), exposure from works (OR = 3.77, 95% CI: 1.49 to 9 , 54, p = 0.005) and the presence of rat (OR = 3.58, 95% CI: 1.35 to 9.49, p = 0.010). Conclusion: Characteristics of cluster formation region is close to the rice field area, a densely populated residential houses at a distance is very close (less than 20 meters). The most dominant risk factor is a house sanitation and presence of rat.